Social movements and protest - Edwards, Gemma (Cambridge Cambridge University Press, 2014)
"This lively textbook integrates theory and methodology into the study of social movements, and includes contemporary case studies to engage students and encourage them to apply theories critically. A wide range of protest cases are explored, from American, European and global arenas, including contemporary examples of political violence and terrorism, alter-globalisation, social networking and global activism. Key chapter features encourage students to engage critically with the material: method points uncover the methodology behind the theories, helping students to understand the larger study of social movements; debate points highlight classic arguments in social movement studies, encouraging students to critically assess theoretical approaches; and case studies connect theories to cases, allowing students to relate key principles to real-world examples. A companion website offers additional student and instructor resources, including lecture slides and worksheets"-- Provided by publisher.
1. Introduction: conceptualizing social movements -- 2. 'From the mad to the sane': collective behavior and its critics -- 3. 'From the rational to the relational': resource mobilization, organization, and social movement networks -- 4. 'From political processes to cultural processes': political opportunity, frames, and contentious politics -- 5. 'From old to new social movements': capitalism, culture, and the reinvention of everyday life -- 6. 'From national to global social movements': network movements, alternative globalization, and new media -- 7. 'From the pretty to the ugly': terrorism, social movement theory, and covert networks -- 8. 'From collective behavior to misbehavior': redrawing the boundaries of political and cultural resistance -- 9. Conclusion: the shifting terrain of social movement studies.
Includes bibliographical references and index.
Keywords: Social movements; Social networks; Globalization -- Social aspects